Regenerative tourism with Crista Valentino - Valentino, Crista, speaker; Hicks, Erin, host; Center for Protected Area Management, producer (Colorado State University. Libraries, 2024)
Episode 6: Is sustainable tourism the best way to think about tourism? What other alternatives and perspectives are out there? In this episode, CPAM's Assistant Director, Erin Hicks, invites you to tune in to the conversation she had with Crista Valentino, Interim Director of the Jackson Hole Travel and Tourism Board in the State of Wyoming, in the United States. Together they discuss the idea of regenerative tourism as an alternative to sustainable tourism, as well as the sustainable tourism destination management plan Crista is involved with.
Protecting hope. Episode 6
Date taken from website.
Accessibility features: Unedited transcript. To request an edited transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: sustainable tourism; regenerative toursim; destination management